A companion to Islamic art and architecture - Flood, Finbarr Barry; Necipoglu, Gulru (Wiley Blackwell companions to art history, 2017)
"This two-volume Companion showcases more than 50 newly commissioned essays that survey Islamic art and architecture in all its traditional grandeur"--